Wavelength-resolved PhotoATRP - Nardi, Martina; Blasco, Eva; Barner-Kowollik, Christopher (Journal of the American Chemical Society, 2022)
The careful mapping of photoinduced reversible-deactivation radical polymerizations (RDRP) is a prerequisite for their applications in soft matter materials design. Here, we probe the wavelength-dependent behavior of photochemically induced atom transfer radical polymerization (ATRP) using nanosecond pulsed-laser polymerization (PLP). The photochemical reactivities at identical photon fluxes of methyl acrylate in terms of conversion, number-average molecular weight, and dispersity of the resulting polymers are mapped against the absorption spectrum of the copper(II) catalyst in the range of 305-550 nm. We observe a red shift of the action spectrum relative to the absorption spectrum of the copper(II) catalyst. Both the number-average molecular weight and the dispersity show a wavelength dependence, while the molecular weight and conversion remain linearly correlated. The reported data allow the judicious selection of optimum wavelengths for photoATRP.
Gesehen am 03.05.2022